Simulasi Pengaruh Ketebalan Elektroda Terhadap Potensial Elektrolit dan Molaritas Spesies Vanadium Redox Flow Battery (VRFB) - Satria Pamungkas Panji Kumara; Irvan Fajar Hidayah; Silvi Hadila; Ervinka Felindia; Nikita Syaharani; Mauludi Ariesto Pamungkas; Kurriawan Budi Pranata; Alamsyah Mohammad Juwono; Muhammad Ghufron (Jurnal Fisika Flux: Jurnal Ilmiah Fisika FMIPA Universitas Lambung Mangkurat, 2022)
Vanadium Redox Flow Battery (VRFB) is a relative new type of secondary battery that has ability as Energy Storage System (ESS) for renewable energy power plants such as solar cell. 2D VRFB single cell was modeled using COMSOL Multiphysics software and simulated numerically by using Nernst-Planck, secondary current distribution, tertiary current distribution and Buttler-Volmer principle. Simulation was conducted at 293,15 K, with electrode thickness variations of 1 mm (L1), 2 mm (L2), 3 mm (L3), 4 mm (L4) and 5 mm (L5). According to the simulation results, it is known that electrolyte potential in negative electrode is higher than positive electrode and the distribution is tend to decrease for all variations.  Surface concentration near collector is dominant during charging compare inlet position and the reverse phenomenon occur during discharging process. VRFB L1 show weak performance and VRFB L2 show the best performance in term of electrolyte potential and species molarity in the electrode surface.